2018
DOI: 10.1038/s41467-018-05064-0
|View full text |Cite
|
Sign up to set email alerts
|

ETS transcription factors induce a unique UV damage signature that drives recurrent mutagenesis in melanoma

Abstract: Recurrent mutations are frequently associated with transcription factor (TF) binding sites (TFBS) in melanoma, but the mechanism driving mutagenesis at TFBS is unclear. Here, we use a method called CPD-seq to map the distribution of UV-induced cyclobutane pyrimidine dimers (CPDs) across the human genome at single nucleotide resolution. Our results indicate that CPD lesions are elevated at active TFBS, an effect that is primarily due to E26 transformation-specific (ETS) TFs. We show that ETS TFs induce a unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
224
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 127 publications
(249 citation statements)
references
References 56 publications
22
224
3
Order By: Relevance
“…Assessment of signals of selection in cancer involves determination of expected mutation rates/probabilities, which may be improved by considering mutational signatures 4 . When applied to recurrent promoter mutations, common in melanoma 31,32 , we found that a regular trinucleotide model failed to give higher mutation probability estimates for non-TERT recurrent sites, generally believed to be passengers [12][13][14][15] , compared to TERT promoter mutations (C228T and C250T) 33,34 , which are established drivers (Fig. 5e).…”
Section: Improved Uv Signature Modeling By Addition Of Longer Contextmentioning
confidence: 97%
See 4 more Smart Citations
“…Assessment of signals of selection in cancer involves determination of expected mutation rates/probabilities, which may be improved by considering mutational signatures 4 . When applied to recurrent promoter mutations, common in melanoma 31,32 , we found that a regular trinucleotide model failed to give higher mutation probability estimates for non-TERT recurrent sites, generally believed to be passengers [12][13][14][15] , compared to TERT promoter mutations (C228T and C250T) 33,34 , which are established drivers (Fig. 5e).…”
Section: Improved Uv Signature Modeling By Addition Of Longer Contextmentioning
confidence: 97%
“…Notably, it has been shown that 5mC facilitates CPD formation by UVB (280-315 nm), the main inducer of CPDs in sunlight, but not by UVC (100-280 nm) 25,26 , which does not penetrate the atmosphere. Despite this, genome-wide studies of CPD formation in human cells to date have all been performed using UVC 14,15,27,28 . To address this, we mapped CPDs genome-wide in human A375 melanoma cells immediately following exposure to UVB (310 nm), using a protocol based on T4 endonuclease V digestion and Illumina sequencing as described previously for UVC 15 (Fig.…”
Section: Reduced Pyrimidine Dimer Formation By Uvb In Promoters Withmentioning
confidence: 99%
See 3 more Smart Citations